2018
DOI: 10.5761/atcs.cr.17-00131
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid Carcinoma of Arising from a Bronchogenic Cyst of the Diaphragm

Abstract: Introduction: Bronchogenic cysts may rupture or become infected, and malignant degeneration may occur. Although various types of malignant degeneration have been described, only a few reports of mucoepidermoid carcinoma arising from a bronchogenic cyst have been published. We report such a case.Case: A 77-year-old female was referred to our institution for evaluation of left chest pain. A computed tomography scan showed an enhancing 65 × 70 mm mass of the left diaphragm. Based on the intraoperative findings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Symptoms may be related to infection of the cyst (58). Surgical resection is generally recommended, even in asymptomatic patients, to establish the diagnosis and prevent complications such as infection, hemorrhage, or rarely, malignant transformation (59).…”
Section: Foregut Duplication Cystmentioning
confidence: 99%
“…Symptoms may be related to infection of the cyst (58). Surgical resection is generally recommended, even in asymptomatic patients, to establish the diagnosis and prevent complications such as infection, hemorrhage, or rarely, malignant transformation (59).…”
Section: Foregut Duplication Cystmentioning
confidence: 99%
“…Bronchogenic cysts are considered to be caused by an aberrant germination or the abandonment of a tracheobronchial rudiment originating from the ventral lung bud of the foregut, during the embryonic period [7]. Most bronchogenic cysts occur in the lungs and mediastinum and rarely arise from the diaphragm [1,2]. The site of occurrence of bronchogenic cysts depends on their timing of development during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the treatment for suspected bronchogenic cysts is surgical removal. Early surgical excision is preferred because, making a definitive preoperative diagnosis is difficult in some cases, the risk of surgery is higher after the appearance of symptoms, and parts of the cyst have been reported to be malignant in previous studies [[2], [3], [4], [5]]. Some studies have suggested a conservative follow-up of asymptomatic patients with suspected bronchogenic cysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramural bronchogenic cysts in the gastroesophageal junction are extremely rare (only 6 cases have been reported in the English literature) (27)(28)(29)(30)(31)(32), and because of the rarity of intramural bronchogenic cysts in the esophagus and gastroesophageal junction, their unique clinicopathological features have not been well recognized. The treatment strategy for bronchogenic cyst is complete excision to avoid recurrence and rare malignant transformation (33,34). Therefore, accurate pre-operative diagnosis is very important for treatment.…”
Section: Introductionmentioning
confidence: 99%